Risiko Gangguan Perkembangan Pada Balita Yang Mengalami Kematian Maternal - Widjianingsih, Elok; Suryawan, Ahmad; Maramis, Margarita M. (Jurnal Keperawatan Muhammadiyah, 2018)
Mortality towards pregnant and maternity women still turns out to be a great problem in Indonesia. According to Indonesia’s Demographic and Health survey in 2012, Indonesia as the country with the highest mortality rate in Southeast Asia. Maternal mortality has short-term and long-term consequences, and those consequences are more significant than mother’s non-maternal mortality of women with reproductive age. Maternal mortality causes the shifting of parenting towards toddlers who are left behind. This can increase the risks of developmental disorders towards toddlers due the lack of focus of the caregivers on the toddlers, consequently the stimulation will be reduced as well. This research aims to analyze whether maternal mortality increases the risks of developmental disorders towards toddlers. The method was using comparative study with retrospective cohort study approach. The research subjects were 41 toddlers who experienced maternal mortality in Probolinggo Regency (case group), and 41 toddlers who did not experience maternal mortality (control group). On the samples, the assessment of the suitability of development stages based on age appropriate KPSP forms. The statistical examination indicates that there is a difference of developmental disorder between case group and control group with p = 0,023 (<0,05), and RR = 2,5. Research conclution indicates that maternal mortality increases the risks of developmental disorder towards toddlers by 2,5 times.